Application of Eight-step Methodology for Reviving Springs and Improving Springshed Management in the Mid-hills of Nepal. - Shrestha, R.; Desai, J.; Mukherji, A.; Dhakal, M.; Kulkarni, H.; Acharya, S. (CGIAR Research Program on Water, Land and Ecosystems, 2017)
Springs are the main source of water for millions of people in the mid-hills of the Hindu Kush Himalaya (HKH). Both rural and urban communities depend on springs to meet their drinking, domestic and agricultural water needs. There is increasing evidence that springs are drying up, or their discharge is reducing throughout the HKH. As a result, communities are facing unprecedented water stress. The exact extent of this problem is not well known, given the dearth of scientific studies. Springs are an integral part of the groundwater system. However, the science of hydrogeology that governs the occurrence and movement of water in underground aquifers is not well understood in regions that depend upon springs. This often results in misconceptions regarding springs. This, in turn, creates misaligned policies that exacerbate the problem. Springs are also part of complex sociotechnical and informal governance systems with pronounced gender and equity dimensions, and these systems are not well understood. Again, such lack to understanding leads to inappropriate policies and interventions. Climate change and change in biophysical landscape (e.g. land-use and vegetation) are widely implicated in the drying of springs. But there is very little systematic knowledge to effectively link climate change, vegetation change and spring discharge, especially because of large data uncertainties. This is an urgent area for research and knowledge generation. Rapid socio-economic and demographic changes and infrastructure (dams, roads etc.) have also impacted springs. But again, the exact nature of change is difficult to understand due to a dearth of studies. This is another important knowledge gap that needs to be filled. The drying of springs, which comes with its own set of consequences, is a regional phenomenon that cuts across the HKH – from Afghanistan all the way to Myanmar. A few local and national organizations have started scientific studies and policy advocacy on springs, but more needs to done, especially given the extent of the problem and its regional and local dimensions. In this context, ICIMOD with support from CGIAR’s WLE Program, has initiated work on understanding the physical and governance issues related to springshed management and use this knowledge to influence policymaking in the region.